Chromatin and regulatory differentiation between bundle sheath and mesophyll cells in maize. (15th December 2021) - Dai, Xiuru; Tu, Xiaoyu; Du, Baijuan; Dong, Pengfei; Sun, Shilei; Wang, Xianglan; Sun, Jing; Li, Gang; Lu, Tiegang; Zhong, Silin; Li, Pinghua
SUMMARY: C4 plants partition photosynthesis enzymes between the bundle sheath (BS) and the mesophyll (M) cells for the better delivery of CO2 to RuBisCO and to reduce photorespiration. To better understand how C4 photosynthesis is regulated at the transcriptional level, we performed RNA‐seq, ATAC‐seq, ChIP‐seq and Bisulfite‐seq (BS‐seq) on BS and M cells isolated from maize leaves. By integrating differentially expressed genes with chromatin features, we found that chromatin accessibility coordinates with epigenetic features, especially H3K27me3 modification and CHH methylation, to regulate cell type‐preferentially enriched gene expression. Not only the chromatin‐accessible regions (ACRs) proximal to the genes (pACRs) but also the distal ACRs (dACRs) are determinants of cell type‐preferentially enriched expression. We further identified cell type‐preferentially enriched motifs, e.g. AAAG for BS cells and TGACC/T for M cells, and determined their corresponding transcription factors: DOFs and WRKYs. The complex interaction between cis and trans factors in the preferential expression of C4 genes was also observed. Interestingly, cell type‐preferentially enriched gene expression can be fine‐tuned by the coordination of multiple chromatin features. Such coordination may be critical in ensuring the cell type‐specific function of key C4 genes. Based on the observed cell type‐preferentially enriched expression pattern and coordinated chromatin features, we predicted a set of functionally unknown genes, e.g. Zm00001d042050 and Zm00001d040659, to be potential key C4 genes. Our findings provide deep insight into the architectures associated with C4 gene expression and could serve as a valuable resource to further identify the regulatory mechanisms present in C4 species. Significance Statement: C4 plants have better light‐use efficiency than C3 as they partition photosynthetic enzymes between the bundle sheath and the mesophyll cells to concentrate CO2 around RuBisCO. To understand the regulatory mechanisms behind this process, we investigated chromatin and regulatory differentiation between bundle sheath and mesophyll cells in maize leaves and found that chromatin accessibility coordinates with epigenetic features to fine‐tune cell type‐preferentially enriched gene expression.